IMPACT OF MSMES GROWTH AND RECOVERY STRATEGY DUE TO COVID-19 - Eka Purwanda (Jurnal Ekonomi, 2021)
Micro, small, and medium-sized companies (MSME) are the major engines of the Indonesian economy, and they have shown again and again to endure all types of economic storms. However, with the COVID-19 epidemic that has decimated many sectors of life throughout the globe, MSMEs are now facing a worldwide issue. As a consequence of constraints, the reduction in MSME Sector Turnover is unavoidable. The goal of this research is to determine the effects and obstacles experienced by the MSME sector, as well as recovery methods that may be implemented as a consequence of COVID-19. This study used the descriptive technique, including descriptive analysis of research findings. The study's findings indicate that the present COVID-19 epidemic has had a significant impact on the MSME sector, and that this has a significant impact on Indonesia's overall economic development. The social restriction policy (PSBB) in particular has led in severe decreases in sales, difficulty in marketing goods, finance or capital challenges, diminished manufacturing and distribution activities, and difficulties in getting raw materials. The authors of this study propose anticipatory steps that the government can take in an effort to prevent the decline of MSMEs, namely that with the government being more focused on recovery efforts by making regulations that help the UMM Sector, the government must ensure that the flow of companies entering and leaving is carried out in stages and in an appropriate manner. Finally, the government is making itself more available to MSME players who can boost economic resilience..